Elaboração e uso de material didático manipulativo para explorar conceitos de cinemática vetorial: uma proposta para o ensino fundamental - Gontijo, Ivaldo Amaral (2017)
This work contemplates the elaboration and development of a didactic unit for the 9th year of elementary education involving the formalization of vector concepts in the teaching of kinematics. To give theoretical support to the research was used the Significative Learning Theory, proposed by Ausubel and as methodology of work the Resolution Problems, proposed by Polya. As didactic strategy we used the activities in groups, activities with the potential to exchange meanings among the students and facilitate the mediation between students and teacher. Among the didactic means used are the use of manipulative materials, elaborated by the authors of the work, from low-cost materials such as battens and PVC pipes. The activities that make up the didactic unit were planned from the perspective of a student with a reflexive and active posture towards a certain problem aiming with this an effective participation of the same in the process of construction of his own knowledge, that is, it is expected that the student feels protagonist in the process of building their knowledge and not mere support. The didactic unit was developed and analyzed in a class of 25 students of the 9th grade of E. E. Chico Marçal, in the city of Moema MG during seven lectures of fifty minutes. The impact of the proposal is described and evaluated throughout this work.